Environmental endocrine disruptor-induced mitochondrial dysfunction: a potential mechanism underlying diabetes and its complications - He, Kunhui; Chen, Rumeng; Xu, Shuling; Ding, Yining; Wu, Zhu; Bao, Meihua; He, Binsheng; Li, Sen (Frontiers in Endocrinology, 2024)
Diabetes and its complications significantly affect individuals' quality of life. The etiology of diabetes mellitus and its associated complications is complex and not yet fully understood. There is an increasing emphasis on investigating the effects of endocrine disruptors on diabetes, as these substances can impact cellular processes, energy production, and utilization, ultimately leading to disturbances in energy homeostasis. Mitochondria play a crucial role in cellular energy generation, and any impairment in these organelles can increase susceptibility to diabetes. This review examines the most recent epidemiological and pathogenic evidence concerning the link between endocrine disruptors and diabetes, including its complications. The analysis suggests that endocrine disruptor-induced mitochondrial dysfunction—characterized by disruptions in the mitochondrial electron transport chain, dysregulation of calcium ions (Ca2+), overproduction of reactive oxygen species (ROS), and initiation of signaling pathways related to mitochondrial apoptosis—may be key mechanisms connecting endocrine disruptors to the development of diabetes and its complications.